Data management : database and organizations - Watson, Richard Thomas (New York : John Wiley and Sons, 1999)
The managerial perspective. Data modeling and SQL. Database architectures and implementations. Organizational memory technologies. Managing organizational memory.
Keywords: Computer; Database management; Database management